Enhancement of spin-orbit torque in Pt/Co/HfOx heterostructures with voltage-controlled oxygen ion migration - Wu, Shuo (2023)
Spin-orbit torque (SOT) induced magnetization switching and SOT modulation by interfacial coupling exhibit good potential in spintronic devices. In this work, we report the enhancement of damping-like field and SOT efficiency of up to 60% and 23%, respectively, in perpendicularly magnetized Pt/Co/HfOx heterostructures over a Pt/Co system at an optimal thickness of 2 nm HfOx. The SOT improvement is primarily attributed to the interfacial oxidization of the Co layer, and the strength is tunable via voltage-induced oxygen ion migration at the Co/HfOx interface. Our measurement reveals that by controlling gate voltages, the Co oxidation can be increased, which leads to the SOT efficiency enhancement. Our work promotes the SOT enhancement and modulation by oxidation effects for energy-efficient spintronic devices.